Galanin mediates tumor-induced immunosuppression in head and neck squamous cell carcinoma - de Medeiros, Marcell Costa; Liu, Min; Banerjee, Rajat; Bellile, Emily; D’Silva, Nisha J.; Rossa, Carlos [UNESP] (Springer Nature, 2022)
Purpose: Galanin receptor 2 (GALR2) plays a significant role in the progression of head and neck squamous cell carcinomas (HNSCC). Since there is virtually no information on immunomodulation mediated by its ligand in the tumor microenvironment, we assessed the effects of galanin on peripheral blood mononuclear cells (PBMCs). Methods: After verification of GALR2 expression and it activity in PBMCs we evaluated the effect of galanin and conditioned media from HNSCC cell lines silenced for galanin or antibody-depleted, on proliferation, apoptosis, cytokine expression and activation/differentiation of immune cells. Results: We found that galanin alone and as a component of the HNSCC secretome decreased HNSCC cell proliferation and expression of pro-inflammatory cytokines (IFNγ, IL-12, IL-17A, IL-1α, IL-6 and TNF-α), whilst increasing apoptosis and expression of pro-tumoral cytokines/growth factors (IL-10, IL-4, PDGF and GM-CSF). T cell activation (using CD69 as activation marker) and anti-tumoral phenotypes in CD4+ T cells (Th1 and Th17) were found to be suppressed. In vivo, tumor growth was found to be increased in the presence of galanin-stimulated PBMCs. Data from The Cancer Genome Atlas (TCGA) revealed that high expression of galanin was associated with a reduced overall survival of patients with HNSCC. Conclusion: Our data indicate that galanin secreted by HNSCC cells exhibits immune-suppressive and pro-tumoral effects.
Keywords: Galanin; Head and neck cancer; PBMCs; T lymphocytes